Influence of genetics, growth and environment on end-grain splitting of Eucalyptus pellita F. Muell. and effectiveness of split remediation methods - Espey, Manuel (2021)
Eucalyptus pellita is currently the predominant tree species deployed for tree plantation establishment in Sabah and Sarawak, Malaysia. Its low disease susceptibility, good growth and form, and desirable wood properties make E. pellita particularly suitable for plantation development in the wet tropical regions of south-east Asia. In spite the many positive traits, practical field observations indicate that the species is susceptible to end-grain splitting. This study evaluates the occurrence and severity of end-grain splitting in plantation grown E. pellita in Sabah and Sarawak as affected by genetics, environment and growth attributes. The study further evaluates the effectiveness of three split remedial measures. Four existing progeny tree breeding trials were used to carry out the split assessment. Logs from the second thinning were cut into 2.2 m long sections. The end splits were assessed three days later at large and small log end. Three split remedial measures were tested and compared against a control in a separate progeny trial in Sabah. Plastic s-hooks, wax and bitumen emulsions were applied to the cut surface and assessed two weeks later. In this study, E. pellita showed a high tendency towards end-grain splitting. About 96% of all logs showed some signs of splitting on its cross-sectional surface with an average of 2.7 splits per cut surface. In average 9.06% of the log volume is compromised due to end-grain splitting. Three-Quarter Radial Splits were the most frequently observed split types with 64% occurrence rate, followed by Pith to Bark Splits with 27%. End-grain splitting in E. pellita is heritable (h2 = 0.24 at p≤0.05). This implies that about 24% of the observed splitting is due to genetics. The trait endgrain splitting therefore can be altered via genetic selections in breeding programs. End-grain splitting also is found to be significantly related to growth factors such as tree height, diameter at breast height (DBH) and tree volume. Increased growth is associated with an increase in split incidence and severity. The unfavorable relationship between growth and log end-grain splitting requires careful selections of high volume and low split genetic material for breeding purpose. Environmental factors, especially soil texture with varying clay- sandsilt content, were found to have a significant effect on log end-grain splitting as well as on growth comparing different sites. Application of plastic s-hooks reduced significantly (49.62%) split occurrence and severity, while the wax and bitumen end sealers had no effect on reduction of growth strain related splits. The findings suggest that end-grain splitting is caused by heritable, complex genetic–environment–growth interactions.